Valorization of olive mill wastewater for the development of biobased polymer films with antioxidant properties using eco-friendly processes. Issue 11 (14th May 2019) - Akretche, Hassina; Pierre, Guillaume; Moussaoui, Ramdane; Michaud, Philippe; Delattre, Cédric
Abstract : A green chemistry process to produce eco-friendly antioxidant biobased polymer films from olive mill wastewater. Abstract : The objective of this study was to evaluate the potential of olive mill wastewater (OMWW) for the synthesis of a new active food material. OMWW contains a substantial amount of valuable antioxidant phenols which can be recovered for industrial applications as food additives. The aim of the present study was to synthesize phenolic compound–pectin conjugates by adopting two eco-friendly green procedures: a free radical-induced grafting using the H2 O2 /ascorbic acid system and a complexation grafting using CaCl2 . The antioxidant activities of the selected free phenolic compounds (coumaric acid, caffeic acid, tyrosol, OMWW) and of the phenolic compound–pectin biobased films were investigated with the DPPH assay. The content of polyphenol in OMWW was estimated to be 2 g L −1 (in gallic acid equivalent), and the free antioxidant activity of OMWW solutions (from 0.2 to 2 g L −1 of polyphenol (in gallic acid equivalent)) was estimated to be from 60 to 80%. After immobilization processes, the antioxidant activities of each biobased polymer film were efficient and stable for a long contact period. Regarding biobased polymer films using OMWW, the antioxidant activities were estimated to be 61 ± 0.4% and 84 ± 0.8% after 96 h for the CaCl2 grafting method and the free radical grafting method, respectively.